PELUANG USAHA KURIR ONLINE TERHADAP PENINGKATAN EKONOMI DAN PENYERAPAN TENAGA KERJA DI MASA PANDEMI COVID 19 (Studi Kualitatif di Kurir Online Ekspress) - ALIE SADIKIN; DARU SUSANTI (Institut Bisnis Muhammadiyah Bekasi, 2020)
A big impact also occurred on job seekers during the Covid-19 pandemic, the competition for job seekers was very fierce as a result of the increasing number of unemployed. It is predicted that in midApril 2020 there will be a surge in unemployment, therefore during this pandemic, some new job seekers have to compete with people who have lost their jobs due to Covid-19. The increasing number of orders is also supported by the services that provide courier services. This opportunity is taken by a business actor who is involved in an online courier business or with a business name is Kurir Ekspress located in Cikeas. Based on the background of this study, the researcher wants to analyze how the Kurir Ekspress opportunity factor in improving the economy during the Covid 19 pandemic, also how the role of online couriers as an opportunity to absorb labor during the Covid 19 pandemic and whether the innovation / advantages of express couriers in customer satisfaction